Metal-organic frameworks for C6–C8 hydrocarbon separations. Issue 4 (July 2021) - Zhang, Zhaoqiang; Peh, Shing Bo; Kang, Chengjun; Chai, Kungang; Zhao, Dan
Highlights: An overview of metal-organic frameworks (MOFs) for the underexplored adsorptive separation of C6-C8 hydrocarbons is provided. The adsorption and separation mechanisms of C6-C8 hydrocarbons using MOFs are systematically discussed based on the structure-property relationships. The perspectives on the development of novel porous materials for C6-C8 hydrocarbon separations are provided. The effectiveness and scope to translate the design strategies of MOFs into novel sorbents for complicated stream systems are provided. Abstract: Hydrocarbon separations are crucial to the chemical industry for the production of valuable feedstocks. However, their structural and chemical similarities have proven daunting challenges to incumbent separation technologies, which are energy- and capital-intensive. Approaches capable of discerning and exploiting minute differences in isomeric hydrocarbons, in particular, may provide solutions to this problem. Metal-organic frameworks (MOFs) integrating the merits of tunable pore size at sub-angstrom scale and pore chemistry in confined spaces have presented promising prospects in adsorptive separation to recognize the minor differences in gas molecules via the judicious design and functionalization. In this Review, we explore the usage of MOFs for the underexplored adsorptive separation of hydrocarbons in the liquid/vapor phase, especially for C6 and C8 isomers. The in-depth insights into the structure-property relationship and the dominant mechanisms, including host-guest interaction modes for the effective adsorption of C6 and C8 hydrocarbons, are systematically discussed. Finally, the effectiveness and scope to translate such design strategies into other systems and the perspective on future development in MOFs for separation are provided.